IMPROVING SPEAKING SKILLS THROUGH BRITISH PARLIAMENTARY STYLE DEBATE - Anak Agung Ketut Rahadinatha; Ni Wayan Krismayani; Nengah Dwi Handayani (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2020)
Speaking is one of crucial language skills that must be mastered by language learners as well as in learning English. In this study, speaking became the main problem dealt by the students especially the eleventh grade students of SMA PGRI 6. The objective of this study was to figure out whether or not speaking skill could be improved by implementing British Parliamentary style debate in the teaching learning process. The results of the post-test in each cycle pointed out there were significant improvements on the subjects’ speaking after implementing British Parliamentary style debate. In addition, the mean figure of the reflection of each cycle, cycle I and II, was 64.93 in cycle I and 76.37 in cycle II. On the other hand, the subjects responded by giving positive responses toward the implementation of British Parliamentary style debate in teaching and learning process. Thus, the present classroom action research showed that speaking skill of the eleventh-grade students of SMA PGRI 6 Denpasar could be improved by implementing British Parliamentary style debate.